Erythropoietin preconditioning improves clinical and histologic outcome in an acute spinal cord ischemia and reperfusion rabbit model - Simon, Florian Hans Peter; Erhart, Philipp (Journal of vascular surgery, 2016)
Objective - This study examined effects and functional outcome of recombinant human erythropoietin (rhEPO) and carbamylated erythropoietin fusion protein (cEPO-FC) preconditioning in a rabbit model for spinal cord ischemia and resulting paraplegia. This model was chosen because only a small surgical effect is needed to cause paraplegia in rabbits, which facilitates postoperative observation of animals. - Methods - Anesthetized but spontaneously breathing New Zealand White rabbits randomly received cEPO-FC (50 μg/kg; n = 8), rhEPO (5000 IU/kg; n = 10), or vehicle (control; n = 10) 30 minutes before and after infrarenal aortic clamping. Ideal clamping time of 22 minutes was identified from preceding clamping tests (15-25 minutes). Postoperative observation time was 96 hours. Spinal cord function was assessed by neurologic evaluation of hind limb motor function every 12 hours using a modified Tarlov score. Spinal cord tissue damage was evaluated after 96 hours using hematoxylin and eosin, elastica van Gieson, Nissl, Masson-Goldner, and hemosiderin staining. Plasma levels of cell senescence markers stathmin, chitinase 1/3, elongation factor 1-α were determined. - Results - Rabbits that received rhEPO showed significant improvement of spontaneous lower limb movements until 36 hours of reperfusion and improved histologic scores upon examination of the lumbar spinal cord compared with the control group. In contrast, cEPO-FC treatment showed comparable outcome to the control group concerning movements of the lower limbs and histology. Senescence markers were elevated in the control group, but not in the treatment groups, except for chitinase 3 in the rhEPO group. Only stathmin showed no significant effect. Markers for senescence might increase after acute ischemic injury. Attenuation of senescence markers might not come alone from improvement of the spinal cord. - Conclusions - Preconditioning with rhEPO attenuates ischemia/reperfusion injury of the spinal cord, whereas the carbamylated derivative (cEPO-FC) showed no positive effect on spinal cord function.
Available online 21 November 2015
Gesehen am 08.05.2020